Effects of Alendronate, Calcitonin and Raloxifene Used in the Treatment of Postmenopausal Osteoporosis On Serum No Levels - Saliha Karatay; Ahmet Kızıltunç; Meltem Alkan Melikoğlu; Gürhan Güreser; Berna Demircan; Kazım Şenel (Galenos Yayinevi, 2005)
The aim of the present study was to evaluate the effects of alendronate, calcitonin and raloxifene used in the treatment of postmenopausal osteoporosis on serum nitric oxide (NO) levels. One hundred women with postmenopausal osteoporosis were enrolled and treated during the 6 months in this study. Patients were equally randomized into four groups: calcitonin, alendronate, raloxifene and control groups. All patients in these three groups and in the control group were supplemented with calcium 500 mg/day elemental calcium. Serum NO levels were determined at baseline and at 6 months. There were not significant changes on serum NO levels after the calcitonin, alendronate, raloxifene and calcium treatment. Also, no significant difference was found among any group comparisons in terms NO levels (p> 0.05). In conclusion, alendronate, calcitonin and raloxifene treatments may not cause to significant changes on serum NO levels.